The effect of freeze-dried Carica papaya leaf juice treatment on NS1 and viremia levels in dengue fever mice model - Mohd Ridzuan Mohd Abd Razak; Norazlan Mohmad Misnan; Nur Hana Md Jelas; Nor Azrina Norahmad; Amirrudin Muhammad; Tiffiny Chau Dee Ho; Bazilah Jusoh; Umi Rubiah Sastu; Murizal Zainol; Mohd Isa Wasiman; Hussin Muhammad; Ravindran Thayan; et al. (BMC, 2018)
Abstract Background Carica papaya leaf juice (CPLJ) was well known for its thrombocytosis activity in rodents and dengue patients. However, the effect of CPLJ treatment on other parameters that could contribute to dengue pathogenesis such as nonstructural protein 1 (NS1) production and viremia level have never been highlighted in any clinical and in vivo studies. The aim of this study is to investigate the effect of freeze-dried CPLJ treatment on NS1 and viremia levels of dengue fever mouse model. Methods The dengue infection in mouse model was established by inoculation of non-mouse adapted New Guinea C strain dengue virus (DEN-2) in AG129 mice. The freeze-dried CPLJ compounds were identified by Ultra-High Performance Liquid Chromatography High Resolution Accurate Mass Spectrometry analysis. The infected AG129 mice were orally treated with 500 mg/kg/day and 1000 mg/kg/day of freeze-dried CPLJ, starting on day 1 post infection for 3 consecutive days. The blood samples were collected from submandibular vein for plasma NS1 assay and quantitation of viral RNA level by quantitative reverse transcription PCR. Results The AG129 mice infected with dengue virus showed marked increase in the production of plasma NS1, which was detectable on day 1 post infection, peaked on day 3 post-infection and started to decline from day 5 post infection. The infection also caused splenomegaly. Twenty-four compounds were identified in the freeze-dried CPLJ. Oral treatment with 500 mg/kg/day and 1000 mg/kg/day of freeze-dried CPLJ did not affect the plasma NS1 and dengue viral RNA levels. However, the morbidity level of infected AG129 mice were slightly decreased when treated with freeze-dried CPLJ. Conclusion Oral treatment of 500 mg/kg/day and 1000 mg/kg/day of freeze-dried CPLJ at the onset of viremia did not affect the plasma NS1 and viral RNA levels in AG129 mice infected with non-mouse adapted New Guinea C strain dengue virus.